Active Learning Strategy Through Peer Lesson: An Effort to Instill Positive Behavior in Elementary School - Darfi Hani; Sugiatno Sugiatno; Rini Rini; Idi Warsah (IAIN Palopo, 2020)
The current study aimed to find a portrayal of learning activities held by teachers using a peer lesson strategy in grade VI students at SDN 02 Lebong Sakti. This study used a qualitative approach, and the teachers at the aforesaid school were involved as the key informants. The data were collected using virtual interviews because this study took place in the period of co-19 pandemic. This study concluded that: The application of peer lesson method conducted by teachers, especially Islamic education teachers, not only gave a new color to students so that they could engage in learning, but also could have a positive impact on the formation of students’ behavior, such as: having independence in learning, getting increases in curiosity and the courage to raise opinions in front of the class in a polite manner, experiencing high enthusiasm, and building up mutual respect for fellow students.